2014
DOI: 10.1002/app.41219
|View full text |Cite
|
Sign up to set email alerts
|

Controlling water permeability of composite films of polylactide acid, cellulose, and xyloglucan

Abstract: To test the hypothesis that the introduction of a hydrophilic hemicellulose would affect viscoelastic properties and increase water permeability, xyloglucan (XG) was adsorbed onto the surface of microcrystalline cellulose (MCC) in water dispersion prior to the extrusion of 79–80 wt % polylactide acid (PLA), 20 wt % MCC, and 0–1 wt % XG. For comparison, composites of PLA, MCC, and non‐absorbed XG were produced. Analysis of thermal properties showed no differences for glass‐transition or melting temperatures, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The heating was stopped at 300 °C; therefore, the exotherms were not compared initially. Presumably, the changes in melting enthalpies can be attributed to modifications in the degree of crystallinity due to grafting copolymerization [ 37 ]. The second approach showed endothermic and exothermic valleys (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…The heating was stopped at 300 °C; therefore, the exotherms were not compared initially. Presumably, the changes in melting enthalpies can be attributed to modifications in the degree of crystallinity due to grafting copolymerization [ 37 ]. The second approach showed endothermic and exothermic valleys (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…The storage modulus of the composite materials increases with xyloglucan content. It also increases water permeability …”
Section: Reinforcing Pla‐based Materials Through Nanocompositesmentioning
confidence: 99%
“…It also increases water permeability. [104] Starch-based PLA composites are also common. [105][106][107] Most often, starch is modified with hydrophobic side chains.…”
Section: Pla Green Compositesmentioning
confidence: 99%
“…They suggest that this fact is explained by the nucleation action of the organoclay, contributing to spontaneous crystallization of the PLA. Gårdebjer, S. et al recently reported also an increase in crystallinity of extruded PLA adding microcrystalline cellulose and xyloglucan [55].…”
Section: Differential Scanning Calorimetry (Dsc) and Gel Permeation Cmentioning
confidence: 99%